THE ROLE OF FOREIGN WORKERS POST JOB CREATION ACT - Mursyid, Besse Tenriabeng (Program Studi Hukum Ekonomi Syariah, Fakultas Syariah, Universitas Islam Negeri (UIN) Datokarama Palu, 2023)
The increasing number of Foreign Workers (TKA) each year, particularly in Central Sulawesi, is undoubtedly a phenomenon contributing to the disparity amidst the persistently high unemployment rates in the region. The role of the government is increasingly crucial in ensuring harmony, fairness, and the fulfillment of rights for every worker in Indonesia. However, the Job Creation Act has changed the regulations governing foreign workers by relevant institutions, from ministries to local offices. This research aims to analyze the position of foreign workers entering Indonesia. The research method employed is Juridical Normative research, which examines the position of foreign workers after enacting the Job Creation Act and explores the changes that have occurred. The research utilizes legal and analytical approaches. The findings indicate that the position of foreign workers after the enactment of the Job Creation Act provides legal certainty for the rights of all workers, regardless of whether they are foreign workers (TKA) or Indonesian workers (TKI). However, the Job Creation Act introduces new regulations regarding administrative provisions, as the permit for employing foreign workers (IMTA) has now been revoked by the Job Creation Act. Abstrak Tingginya jumlah Tenaga Kerja Asing (TKA) yang setiap tahunnya semakin meningkat di Indonesia khususnya di wilayah Sulawesi Tengah tentunya menjadi fenomena ketimpangan terhadap masih tingginya jumlah pengangguran di wilayah Sulawesi Tengah, peran pemerintah tentu semakin banyak terkait pengaturan agar tercipta keselarasan, keadilan serta jaminan terpenuhinya hak bagi setiap pekerja yang berkedudukan di Indonesia pada umumnya. akan tetapi keberadaan Undang-Undang Cipta Kerja terdapat perubahan pengaturan TKA oleh lembaga terkait dalam hal ini kementrian hingga dinas. Tujuan penelitian ini untuk menganalisis kedudukan TKA yang masuk di Indonesia. Adapun metode penelitian yang digunakan ini yaitu penelitian Yuridis Normatif, dimana penelitian ini akan mengkaji kedudukan TKA pasca keberadaan Undang-Undang Cipta Kerja yang telah mengalami perubahan, serta penelitian ini menggunakan pendekatan Undang-Undang dan Analistis. Hasil penelitian menunjukan bahwa kedudukan TKA pasca keberadaan Undang-Undang Cipta Kerja bahwa undang-undang memberikan kepastian hukum terhadap hak-hak tenaga kerja tanpa melihat TKA maupun TKI, akan tetapi Undang-Undang Cipta memberikan pengaturan baru terkait ketentuan administratif sebab IMTA (Izin Mempekerjakan TKA) kini telah dicabut oleh Undang-Undang Cipta Kerja.